An in vitro study of stereoselectivity of cytochrome p450 enzymes in the metabolism of 3,4-methylenedioxymethamphetamine - Asim, Wan Raihana Wan Aasim @ Wan (2013)
Cytochrome P450 (CYP) enzymes metabolise 3,4- methylenedioxymethamphetamine (MDMA). MDMA is a neurotoxic drug of abuse with stimulant and hallucinogenic properties. Its metabolism is stereoselective with (S)-MDMA preferred over (fl)-MDMA. Since MDMA stereoisomers possess different pharmacokinetic and pharmacodynamic properties, stereoselective metabolism plays an important role in the acute and chronic effects of MDMA. This study utilises an in vitro approach to identify if stereoselective metabolism of MDMA is influenced by: i) inter-individual variations or CYP polymorphisms and ii) inhibition of CYP enzymes. A novel stereoselective method for gas chromatography-mass spectrometry analysis of MDMA and metabolites was developed, optimised and validated. The method was applied in subsequent experiments. The in vitro study had three parts: i) determination of MDMA stereoselective protein binding in humans, rats and mice, ii) a correlation analysis study using human liver microsomes (HLM) to determine the effect of inter-individual variations and CYP polymorphisms on MDMA stereoselective metabolism, and iii) enzyme inhibition experiments to study the effects on stereoselectivity. The analytical method was successfully validated. The method was linear from 10 to 1000 pg/L for MDMA, 3,4-dihydroxymethamphetamine (HHMA) and 4- methoxy-3-hydroxymethamphetamine and from 1 to 100 pg/L for 3,4- methylenedioxyamphetamine, 3,4-dihydroxyamphetamine and 4-methoxy-3- hydroxyamphetamine with correlation coefficients, R" of > 0.991 for all analytes. Intra- and inter-day precisions were < 12% for all concentrations and recoveries were > 89% for all analytes. Total MDMA protein binding was 41 - 51% in humans, 38 - 50% in rats and 11 - 36% in mice. Protein binding was not stereoselective in humans or rats, however significant (p<0.05) stereoselective binding occurred in mice. In mice, (S)-MDMA is preferentially bound over (7?)-MDMA, resulting in (7?)- versus (S)-enantiomer ratios of 0.78 at 20 pg/L MDMA and 0.74 at 200 pg/L MDMA. Several correlations between CYP enzymes and MDMA stereoselective metabolism were identified. HHMA formation was positively correlated with CYP2D6 activity and HHMA enantiomer ratios were negatively correlated with CYP2D6 activity, MDMA substrate concentrations and age. Inhibition of CYP enzymes decreased HHMA formation. The inhibition experiments indicated CYP2D6, CYP1A2, CYP2C19 and CYP2B6 are responsible for HHMA formation. Additionally, inhibition did not significantly alter stereoselectivity. Stereoselectivity in protein binding does not contribute towards stereoselective metabolism of MDMA. Instead, stereoselective metabolism is due to CYP2D6 as the primary enzyme and CYP1A2, CYP2C19 and CYP2B6 to a lesser extent. Interestingly, stereoselectivity was negatively correlated with CYP2D6 activities, age and concentration of MDMA. Additionally, enzyme inhibition did not alter stereoselectivity.